Optimization of a calcium-dependent Protein A-derived domain for mild antibody purification. Issue 8 (17th November 2019) - Scheffel, Julia; Kanje, Sara; Borin, Jesper; Hober, Sophia
ABSTRACT: As reported here, we developed and optimized a purification matrix based on a Protein A-derived domain, ZCa, displaying calcium-dependent antibody binding. It provides an alternative to the acidic elution conditions of conventional Protein A affinity chromatography for purification of sensitive antibodies and other Fc-based molecules. We describe the multimerization of ZCa to generate a chromatography resin with higher binding capacity. The highest order multimeric variant, ZCa TetraCys, demonstrated a considerably high dynamic binding capacity (35 mg IgG/ml resin) while preserving the specificity for IgG. High recovery was obtained and host cell protein and DNA content in purified fractions proved to be comparable to commercial MabSelect SuRe and MabSelect PrismA. Various elution conditions for use of this domain in antibody purification were investigated. The purification data presented here revealed variations in the interaction of different subclasses of human IgG with ZCa TetraCys. This resulted in diverse elution properties for the different IgGs, where complete elution of all captured antibody for IgG2 and IgG4 was possible at neutral pH. This optimized protein ligand and the proposed purification method offer a unique strategy for effective and mild purification of antibodies and Fc-fusion proteins that cannot be purified under conventional acidic elution conditions due to aggregation formation or loss of function.